2011
DOI: 10.3109/00365548.2011.585179
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of neutrophil volume distribution width to C-reactive protein and procalcitonin as a proposed new marker of acute infection

Abstract: NDW had the highest diagnostic accuracy and is available with the complete blood count with differential (CBC). It may be a promising parameter to aid in the diagnosis of acute infection in adults, provided the possibility of haematological disorders is first ruled out.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
37
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 16 publications
0
37
0
Order By: Relevance
“…We also evaluated the biological variations of leukocyte morphologic parameters or CPD, mainly because of an increasing number of publications [3][4][5][6][7][8][9][10][11][12][13] in recent years demonstrating the potential clinical utility of CPD in diagnosing many pathologic conditions, particularly in acute bacterial infection or sepsis. [3][4][5][6][7][8][9][10] We showed that the CPD have much smaller overall CV I and CV G compared to numerical parameters, suggesting that these morphologic parameters are less variable around the homeostatic set point intraindividually and interindividually. In addition, the index of individuality for all morphologic parameters was low.…”
Section: Commentmentioning
confidence: 99%
See 2 more Smart Citations
“…We also evaluated the biological variations of leukocyte morphologic parameters or CPD, mainly because of an increasing number of publications [3][4][5][6][7][8][9][10][11][12][13] in recent years demonstrating the potential clinical utility of CPD in diagnosing many pathologic conditions, particularly in acute bacterial infection or sepsis. [3][4][5][6][7][8][9][10] We showed that the CPD have much smaller overall CV I and CV G compared to numerical parameters, suggesting that these morphologic parameters are less variable around the homeostatic set point intraindividually and interindividually. In addition, the index of individuality for all morphologic parameters was low.…”
Section: Commentmentioning
confidence: 99%
“…[3][4][5][6][7] The mean neutrophil volume and/or neutrophil volume distribution width, which reflect respectively neutrophil size and size variations, show superior sensitivity and specificity for predicting sepsis compared to WBC, the percentage of neutrophils, band counts, C-reactive protein, or procalcitonin, proving to be promising indicators for the diagnosis of acute bacterial infection. 8,9 In addition, the mean neutrophil volume and neutrophil volume distribution width are significantly increased in postsurgical patients with bacterial infection compared with noninfected patients, although WBC was increased in both groups. 9,10 Alterations of the lymphocyte CPD in viral infection 11,12 and in chronic lymphocytic leukemia and other chronic lymphoproliferative disorders 12 as well as the monocyte CPD in malaria infection 13 have also been reported.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…2 Early diagnosis and appropriate management are critical to reducing mortality. 3 Early diagnosis may be more effective in overall cost containment and outcome than a more specific but late diagnosis. 4 Therefore, a rapid, accurate, and cost-effective test is needed.…”
Section: Introductionmentioning
confidence: 99%
“…4 Therefore, a rapid, accurate, and cost-effective test is needed. 3 However, early diagnosis of sepsis is difficult because the signs and symptoms of sepsis such as fever, are nonspecific and may be blunted or absent. 5 Peripheral blood smears can also yield important diagnostic information by identifying characteristic morphologic changes seen in reactive neutrophils.…”
Section: Introductionmentioning
confidence: 99%